2020
DOI: 10.2147/dmso.s244761
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association of Overweight, Obesity and Abdominal Obesity with Socioeconomic Status and Educational Level in Colombia</p>

Abstract: Objective: Latin American countries are experiencing a nutritional and demographic transition that predisposes to the spread of the obesity epidemic, especially among the socially and economically disadvantaged. We aimed to describe the prevalence of obesity, overweight and abdominal obesity and their association with household socioeconomic status (SES) and personal educational level in the five major cities of Colombia (Bogotá, Medellín, Cali, Barranquilla and Bucaramanga). Materials and Methods: We collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 42 publications
4
22
0
5
Order By: Relevance
“…Additionally, we analyzed a larger sample from urban, suburban, and rural areas to illustrate the prevalence in children in Southwest China, resulting in a more reliable conclusion. We found that children with a better SES (living in urban or suburban areas with a higher father’s education level and higher family income) had a higher prevalence of overweight and obesity than those with a lower SES, a finding that was consistent with other studies [ 28 , 29 ]; however, this result also contrasted with those of other studies [ 30 ] and requires further study to verify the current findings. Yang Liu et al [ 31 ] found a significant protective interaction effect between paternal education and household wealth on the obesity risk in girls but no significant difference in the childhood obesity prevalence in children with different household wealth levels, fathers’ education levels, mothers’ education levels, or residence registration areas, which was inconsistent with our results.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Additionally, we analyzed a larger sample from urban, suburban, and rural areas to illustrate the prevalence in children in Southwest China, resulting in a more reliable conclusion. We found that children with a better SES (living in urban or suburban areas with a higher father’s education level and higher family income) had a higher prevalence of overweight and obesity than those with a lower SES, a finding that was consistent with other studies [ 28 , 29 ]; however, this result also contrasted with those of other studies [ 30 ] and requires further study to verify the current findings. Yang Liu et al [ 31 ] found a significant protective interaction effect between paternal education and household wealth on the obesity risk in girls but no significant difference in the childhood obesity prevalence in children with different household wealth levels, fathers’ education levels, mothers’ education levels, or residence registration areas, which was inconsistent with our results.…”
Section: Discussionsupporting
confidence: 88%
“…The associations between SES and both parental and childhood obesity are controversial. Prior research [ 29 ] revealed a lower SES and educational level increased the risk of adult obesity, while a higher SES was positively correlated with childhood obesity in developed areas. The present study demonstrated that a higher family income and a higher education level are related to an increased risk of parental obesity, and a history of parental obesity contributed to an increased z-BMI, suggesting that children with a high SES (income and father’s education) may gain excess weight because of a history of parental obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Between the 75 th and 105 th day in hyperlipidic swimming rats, the body weight decreases as well as when soymilk was added. This could be explained by its high protein contents; known to build body mass [19,20]. These results are comparable to those obtained on the indicators of overweight and obesity [21], which could be attributed to regular physical exercise combined with soymilk, would normalize body weight and the metabolic dysfunctions induced [22,23].…”
Section: Discussionsupporting
confidence: 55%
“…Conversely, a high proportion of participants were unaware of weight gain (40%), and only 22.3% reported to have gained weight. In Colombia, the increasing prevalence of overweight and obesity is of great concern due to its association with non-communicable chronic diseases, which contribute significantly to the morbidity and mortality of the country's adult population (8,24,25). In fact, the prevalence of overweight and obesity in Colombian adults aged over 18 years is 34.6 and 16.5%, respectively, these rates being higher in women.…”
Section: Discussionmentioning
confidence: 99%